Upgrading CO2 by Incorporating into Quinazolinones: A Review - Wahan, Simranpreet K.; Sharma, Sangeeta; Chawla, Pooja A. (Mini-Reviews in Organic Chemistry, 2023)
Efficient translation of CO2 into value-added compounds is a fascinating topic in green chemistry. The effective conversion of CO2 into useful chemicals and materials helps civilization flourish in the long run. Carbon dioxide has shown tremendous applications by replacing dangerous chemicals like phosgene, isocyanates, or carbon monoxide, resulting in more environment-friendly operations. This article is an overview in which we highlight current advances in synthesizing quinazolinone, a favoured scaffold in the pharmaceutical industry for its therapeutic value in the treatment of various pathologies. The complementarity of succinct methods aids the ability to generate libraries of functionalized quinazolinone derivatives.
Keywords: CO2